Corporate Profit, Social Welfare, and the Logic of Capitalism. (8th September 2016) - Reiter, S. L.
Abstract: Business ethics scholars have proposed strategies for mitigating the ill effects brought on by a wealth maximization business strategy by urging managers to either embrace corporate social responsibility (CSR) or to manage according to stakeholder theory. In this article I argue that these strategies are often ineffective in bringing about the behavior they promote because it is antithetical to the nature and logic of capitalism. I examine the organizing principles of capitalism and the role it assigns to capitalists, and juxtapose these with the behavior prescribed by three normative frameworks: strategic management theory (SMT), the CSR initiative, and stakeholder theory. Unlike the behaviors prescribed by the CSR initiative and stakeholder management theory, the behavior prescribed by SMT is consistent with the role of capitalists as defined by the organizing principles of capitalism, and SMT's "rules" have instilled habits that have, in turn, been able to mold managers' aspirations and purposes. CSR and stakeholder theory must not only combat the habits instilled by the entrenched SMT, they must also find some way of instilling habits that run contrary to those defined by the nature and logic of capitalism itself.